IDENTIFIKASI KEANEKARAGAMAN JENIS ROTAN (Calamus Sp.) DI KAWASAN HUTAN ADAT LEMBAH SENENGGAN DESA DURIAN KAWAN KECAMATAN KLUET TIMUR-ACEH SELATAN - Ahmadi; Hildanus; Kariamansyah (Jurnal Penelitian Hutan dan Sumber Daya Alam (PHSDA), 2022)
The Senenggan Valley Traditional Forest Area, Durian Kawan Village, East KluetDistrict, is located in South Aceh Regency, which is located in Aceh Province. The LeuserEcosystem Area (KEL) is a buffer zone of the Gunung Leuser National Park (TNGL),which has a good collection of rattan with a wide variety of rattan. However, the type andamount of rattan scattered in the area is not yet known. The purpose of this study 1) Todetermine the types of rattan in the Senenggan Valley Traditional Forest, Durian KawanVillage, East Kluet District, South Aceh. 2) To determine the diversity of rattan plantsbased on altitude in the area of the Senenggan Valley Traditional Forest, Durian KawanVillage, East Kluet District, South Aceh. This study used a qualitative method. The resultsof this study indicate 1) There are 6 types of rattan in the Senenggan Valley IndigenousForest area, namely Jernang rattan (Daemonorops didymophylla Becc.), Wax rattan(Calamus javensis Blume.), Manan rattan (Calamus manan Miq.), Taman rattan(Calamus caesius Blume.) Sega Ayer rattan (Calamus caesius. Blume.) and Dahan rattan(Korthalsia rigida Blume.).2) The diversity (H') of rattan species in the Senenggan ValleyIndigenous Forest Area is categorized as low with a Diversity index (H') of 0.73 . 3) Themost common type of rattan is branched rattan (Korthalsia rigida Blume.) with a total of13 rattan sticks